CHARACTERISTIC OF BLUE SWIM CRAB MUSTARD (Portunus Pelagicus) PROTEIN HYDROLYSATE WITH DIFFERENT PAPAIN ENZYME CONCENTRATIONS - Nur Fadilah; Eko Nurcahya Dewi; Romadhon Romadhon; Lukita Purnamayati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Mustard is a waste contain protein produced from the shell stripping process of blue swimming crab. It has a great potential to be processed as protein hydrolysate. Papain enzyme could be a hydrolysis agent due to its specific function and didn’t cause protein damage. The liquid product of the mustard hydrolysate protein requires a drying process to become a powder product. The drying process method is known as foam-mat drying. The research aims to determine the effect of papain enzyme addition on the characteristics of mustard protein hydrolysate from blue swimming crab and the best enzyme concentration. The research method was  used a completely randomized design (CRD) with different enzyme concentration treatments (0%, 5%, 7.5% and 10%). The data obtained were tested using  ANOVA test, in order  to determine differences  between  treatment a  Honestly Significant Difference (HSD) test were applied. The results showed that the addition of different papain enzyme concentrations had a significantly different effect (P<5%) on all test parameters (yield, hydrolysis degree, protein content, moisture content, fat content, ash content, protein digestibility, and amino acid profile). Based on the results of the study, the best mustard hydrolysate protein were the addition of 10% papain enzyme concentration with a yield value of 19.14±0.29%, hydrolysis degrees of 40.19±0.24%, protein content 49.21±0.83% (dw), the moisture content 7.20±0.20%, fat content 1.49±0.29%, ash content 7.22±0.20%, protein digestibility 88.35% and the highest amino acid level was glutamic acid (3.746%).